2020
DOI: 10.1051/e3sconf/202017205010
|View full text |Cite
|
Sign up to set email alerts
|

Air leakage paths in buildings: Typical locations and implications for the air change rate

Abstract: The harsh Norwegian climate requires buildings designed to high standards. An airtight building envelope is crucial to achieve an energy efficient building and to avoid moisture problems. Results from the SINTEF Building defects archive show that a considerable part of the building defects is related to air leakages. In addition, air leakages increase the energy demand of buildings. A literature study has been conducted in order to map typical air leakage paths of Norwegian wooden houses. In order to increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…With the growing demand for energy efficiency in buildings, national construction authorities are strengthening building requirements to mitigate future climate impacts and adapt to them. The research results also indicate that traditional solutions can be further improved by using modern foil materials together with sealing tapes [8,9].…”
Section: Introductionmentioning
confidence: 80%
“…With the growing demand for energy efficiency in buildings, national construction authorities are strengthening building requirements to mitigate future climate impacts and adapt to them. The research results also indicate that traditional solutions can be further improved by using modern foil materials together with sealing tapes [8,9].…”
Section: Introductionmentioning
confidence: 80%
“…The other membrane, i.e., the wind barrier, should be placed on the cold side and should be vapor-permeable to allow moisture to escape from the LSF elements [24]. The most common air leaks found in field measurements in the literature are at the junctions between the exterior wall and ceiling or floor, exterior wall and window or door, and exterior wall and penetrations in the barrier layers [68]. To improve overall airtightness, sealing tapes should also be used in combination with the above-mentioned membranes.…”
Section: Wind and Air Tightness Membranesmentioning
confidence: 99%
“…In cold climates and under a high internal humidity (60% RH at 23 • C), the use of sealing tape alone does not guarantee that the timber joist pockets will retain a relative humidity within the target limit of 85% [13]. A comparison of the various sealing methods has shown that air permeability can be further improved when sealing tape is used, but it is recommended to conduct durability studies and those on the use of tapes to seal all the joints to ensure low-level air permeability [14]. The simulation of wind pressure and rain loads has resulted in water leaks in tape-sealed joints even under low pressure, and water leaked at the intersections of the horizontal-vertical joint without any pressure effect [15].…”
Section: Introductionmentioning
confidence: 99%